2011
DOI: 10.1186/1749-799x-6-52
|View full text |Cite
|
Sign up to set email alerts
|

Oxford unicompartmental knee arthroplasty: medial pain and functional outcome in the medium term

Abstract: BackgroundIn our experience results of the Oxford unicompartmental knee replacement have not been as good as had been expected. A common post operative complaint is of persistent medial knee discomfort, it is not clear why this phenomenon occurs and we have attempted to address this in our study.Methods48 patients were retrospectively identified at a mean of 4.5 years (range = 3 to 6 years) following consecutive Oxford medial Unicompartmental Knee arthroplasties for varus anteromedial osteoarthritis. The mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 19 publications
2
25
0
Order By: Relevance
“…However, persistent postoperative pain (PPOP) has been a common occurrence in about 10-53% of patients after a total knee arthroplasty (TKA) and is associated with reduced health-related quality of life [1]- [5]. Studies regarding unicompartmental knee arthroplasties (UKAs) also reported a high incidence of medial knee discomfort and pain which did not correlate with the postoperative radiographic scores, preoperative arthritis, and the positioning of the prosthesis and might lead to unnecessary revisions [6]- [9]. Many factors may be responsible for a painful knee prosthesis.…”
Section: Introductionmentioning
confidence: 99%
“…However, persistent postoperative pain (PPOP) has been a common occurrence in about 10-53% of patients after a total knee arthroplasty (TKA) and is associated with reduced health-related quality of life [1]- [5]. Studies regarding unicompartmental knee arthroplasties (UKAs) also reported a high incidence of medial knee discomfort and pain which did not correlate with the postoperative radiographic scores, preoperative arthritis, and the positioning of the prosthesis and might lead to unnecessary revisions [6]- [9]. Many factors may be responsible for a painful knee prosthesis.…”
Section: Introductionmentioning
confidence: 99%
“…With regards to loosening but also other causes of failure, at least four aspects of surgical technique have been mentioned: malposition of the implants [2], overhanging of components leading to soft tissue irritation [3], impingement leading to pain , and medial collateral ligament damage leading to subluxation or dislocation of the meniscal bearing or to valgus malalignment [1,2]. Studies trying to detect the influence of single surgical factors, such as implant positioning, have not been conclusive [20,21]. We therefore recommend to address all factors simultaneously by preserving the medial collateral ligament, positioning the femoral jig centrally, maintaining congruity of the femoral drill hole and ensuring osteochondral clearance to accommodate hyperextension.…”
Section: Discussionmentioning
confidence: 99%
“…Patients' satisfaction after knee arthroplasty is variable. High percentages of dissatisfaction considering patients' concerns were reported in both UKA [13] and TKA [14,15]. A comparison study between subjective and objective outcome systems revealed poor correlations, suggesting that the concerns and priorities of patients and surgeons differ [16].…”
Section: Discussionmentioning
confidence: 99%